Europec/Eage Conference and Exhibition 2008
DOI: 10.2118/113821-ms
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion Deposition in Porous Media: Impact on Well Injectivity

Abstract: Emulsions flow is encountered in various pratical applications such as enhanced oil recovery (EOR) processes. The occurence of emulsions can have a detrimental impact on well productivity/injectivity and hence, on the enconomic of many EOR operations. However there is still a lack of clear understanding of how they really behave inside a porous medium. The present work aims at given new insights into emulsion deposition mechanisms. Different experimental conditions are explored to study the deposition of "stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Therefore, the JR values for surface-capture characterization ranged from 45 to 50. In a previous paper (Buret et al 2008), we reported on the results of the first part of this study dedicated to surface-capture investigation. Our results fully supported the colloidal-transport similarity for stable emulsion flow through porous media.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the JR values for surface-capture characterization ranged from 45 to 50. In a previous paper (Buret et al 2008), we reported on the results of the first part of this study dedicated to surface-capture investigation. Our results fully supported the colloidal-transport similarity for stable emulsion flow through porous media.…”
Section: Resultsmentioning
confidence: 99%
“…This value will be tantamount to the initial concentration as long as the droplet size does not evolve. This is described in one of our previous papers (Buret et al 2008).…”
Section: Methods Setup Description As Depicted Inmentioning
confidence: 92%
See 3 more Smart Citations